Miniaturized and Thermal‐Based Measurement System to Measure Moisture in Textile Materials. Issue 13 (22nd April 2020) - Schönfisch, David; Göddel, Michael; Blinn, Jörg; Heyde, Christian; Schlarb, Heiko; Deferme, Wim; Picard, Antoni
Abstract : Moisture in textile materials worn close to the skin greatly influences our daily comfort. The measurement of moisture in textile materials is therefore of great interest, for example, to determine the amount of perspiration in clothing or car seats, the wound fluid in dressings, or even the urine in diapers or bed linen. All these applications require a robust moisture measurement method, which is harmless to humans and measures in thin layers. One method ideally suited to fit these requirements is the transient‐heat moisture sensing (THMS) method. Herein, a miniaturized and evolved adaption of the THMS method is shown. The measurement system presented herein is optimized for low energy consumption and portability. The working principle of this measuring system is demonstrated by conducting a simple test to investigate the transplanar wicking of eight fundamentally different but garment‐typical textiles. The THMS method and its ability to measure in thin layers that is ideally suited to measure moisture in thin layers are shown. Finally, it lays a foundation to enable a multitude of future applications, wherever moisture (e.g., sweat) is to be measured with high accuracy and with a wearable system close to the human skin. Abstract : A moisture measurement method based on a thermal working principle is used to measure moisture in thin textile layers. The lightweight measurement system enables moisture measurements in garment‐typical textiles with low‐energy consumption, high sensitivity, and negligible cross‐influence on temperature, salinity, or environment beyond the textile.